From the body to the psychic envelope: the route of a psychic genesis (Historical-theoretical basis) - Hamlaoui, Amel; KERBOUCHE , Abdelhamid (Journal of Human Sciences, 2022)
The aim of this article is to highlight and redefine the notions of the skin-self and the psychic envelope,returing to certain epistemological contributions we underline :on the one hand ,the importance of the relation schips :body/and psyche as-the beginning of a fundamental journey for all levels of the psychic apparatus and the development of subjectivity. And on the other hand,to highlight the genesis and progression of the concept of the psychic envelope and to shed a different light on this notion,by refering to an approch that theorists are pursuing and developing to move from an analogy supported by a body to a broader clinical conception,scape the trap of analogical thinking.